Systemic leptin produces a long-lasting increase in respiratory motor output in rats - Chang, Zheng; Ballou, Edmund; Jiao, Weijie; McKenna, Kevin E.; Morrison, Shaun F.; McCrimmon, Donald R. (Frontiers in Physiology, 2013)
Leptin decreases food intake and increases energy expenditure. Leptin administration into the CNS of mice or rats increases alveolar ventilation and dysfunction in leptin signaling has been implicated in the hypoventilation that can accompany obesity. An increase in CO2 chemosensitivity has been implicated in this response but it is unclear whether ventilation is augmented when PCO2 is maintained constant. We examined the effects of intravenous leptin to test the hypothesis that systemic leptin administration in isoflurane anesthetized, mechanically ventilated and vagotomized rats would lead to a sustained increase in respiratory motor output that was independent of changes in end-tidal PCO2, body temperature or lung inflation pressure (an indicator of overall lung and chest wall compliance). In anesthetized Sprague-Dawley rats with end-tidal PCO2, lung compliance and rectal temperature maintained constant, injection of a bolus of leptin (0.25 mg, 0.5 mg/ml, i.v.), followed over the next 1 hour by the intravenous infusion of an additional 0.25 mg, elicited a progressive increase in the peak amplitude of integrated phrenic nerve discharge lasting at least 1 hr beyond the end of the infusion. The increase peaked at 90 min at 58.3 ± 5.7% above baseline. There was an associated increase in the slope of the phrenic response to increasing inspired CO2.. There was also a moderate and sustained decrease in arterial pressure 9 ± 1.3 mmHg at 120 min, with no associated change in heart rate. These data indicate that leptin elicits a sustained increase in respiratory motor output that outlasts the administration leptin via a mechanism that does not require alterations in arterial PCO2, body temperature or systemic afferent feedback via the vagus nerves. Leptin may play an important role in matching alveolar ventilation to metabolism.